2015
DOI: 10.1002/app.42237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fly ash cenospheres on performance of coir fiber‐reinforced recycled high‐density polyethylene biocomposites

Abstract: Recycled high-density polyethylene (RHDPE)/coir fiber (CF)-reinforced biocomposites were fabricated using melt blending technique in a twin-screw extruder and the test specimens were prepared in an automatic injection molding machine. Variation in mechanical properties, crystallization behavior, water absorption, and thermal stability with the addition of fly ash cenospheres (FACS) in RHDPE/CF composites were investigated. It was observed that the tensile modulus, flexural strength, flexural modulus, and hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…The rHDPE DMA curves were similar to other curves found in literature. 3034 We noticed a reduction in the E′ values at −100℃ in the overlay of the curves (Figure 10), related to the increase in the filler content of the composites. Most of the curves intersect at −20℃, and we ascribed this temperature to the lower/upper threshold.…”
Section: Resultsmentioning
confidence: 92%
“…The rHDPE DMA curves were similar to other curves found in literature. 3034 We noticed a reduction in the E′ values at −100℃ in the overlay of the curves (Figure 10), related to the increase in the filler content of the composites. Most of the curves intersect at −20℃, and we ascribed this temperature to the lower/upper threshold.…”
Section: Resultsmentioning
confidence: 92%
“…The cellulose content is the source for fiber tensile strength. Lignin surrounds and protects cellulose and acts to increase the stiffness and toughness of the fiber . It also enhances durability with regards to decay in moist environments.…”
Section: Resultsmentioning
confidence: 99%
“…One example of functionalized polyethylene was maleated polyethylene, which was polyethylene grafted with maleic anhydride functional group. Maleated polyethylene had been widely studied in research as a compatibilizing agent for improving the dispersion of different microfillers and nanofillers such as fly ash [14], carbon nanotubes [15], and nanoclays [16] in polyethylene matrix. The above studies confirmed the importance of having MAPE as compatibilizer for improving the dispersion and properties of polyethylene composites.…”
Section: Introductionmentioning
confidence: 99%